Desarrollo de un sistema matemático para la elaboración de tarifas volumétricas en especies arbóreas - Jiménez Pérez, Javier; Aguirre Calderón, Oscar A.; Treviño Garza, Eduardo J.; Domínguez Calleros, Antonio (Instituto de Ecología, A.C., 2016)
In forest ecosystems management it is a primary need to elaborate volume tables and tariffs appropriate for arboreal specimens with economic importance, therefore it turns out to be a fundamental condition in sustainable ecological planning, the establishment of these mensuration systems. The present study is based on the development of a mathematical system to estimate volumes of arboreal species, through the application of an association of mathematical models. The obtained result, after the respective statistical analysis, proves that the use of the volume tariffs for global evaluations within the forest ecosystems represents a tool of great usefulness, by achieving a high precision in considering how valuable the renewable natural resources are.